Mechanisms of enhanced antiglioma efficacy of polysorbate 80‐modified paclitaxel‐loaded PLGA nanoparticles by focused ultrasound. Issue 9 (29th June 2018) - Li, Yingjia; Wu, Manxiang; Zhang, Nisi; Tang, Caiyun; Jiang, Peng; Liu, Xin; Yan, Fei; Zheng, Hairong
Abstract: The presence of blood‐brain barrier (BBB) greatly limits the availability of drugs and their efficacy against glioma. Focused ultrasound (FUS) can induce transient and local BBB opening for enhanced drug delivery. Here, we developed polysorbate 80‐modified paclitaxel‐loaded PLGA nanoparticles (PS‐80‐PTX‐NPs, PPNP) and examined the enhanced local delivery into the brain for glioma treatment by combining with FUS. Our result showed PPNP had good stability, fast drug release rate and significant toxicity to glioma cells. Combined with FUS, PPNP showed a stronger BBB permeation efficiency both in the in vitro and in vivo BBB models. Mechanism studies revealed the disrupted tight junction, reduced P‐glycoprotein expression and ApoE‐dependent PS‐80 permeation collectively contribute to the enhanced drug delivery, resulting in significantly stronger antitumour efficacy and longer survival time in the tumour‐bearing mice. Our study provided a new strategy to efficiently and locally deliver drugs into the brain to treat glioma.